Is Personal Vote‐Seeking Behavior Effective?. Issue 2 (May 2016) - Däubler, Thomas; Bräuninger, Thomas; Brunner, Martin
Abstract : Does representatives' legislative activity have any effect on their electoral performance? A broad theoretical literature suggests so, but real‐world evidence is scarce as empirically, personal and party votes are hard to separate. In this article, we examine whether bill initiation actually helps MPs to attract preference votes under flexible list electoral systems. In these systems, voters can accept the party‐provided rank order or vote for specific candidates, which allows a clear distinction between personal and party votes. The empirical analysis uses data on bill initiation by Belgian MPs in the period 2003–2007 to explain their personal vote in the 2007 elections. We find that particularly single‐authored proposals initiated shortly before the upcoming elections are associated with a larger personal vote.